Assessment of Students' Knowledge in Medical Technical Institute/Baghdad about Tuberculosis diseases - Eman Mahmud Ismail Al Ramahy (Kufa Journal for Nursing Sciences)
Objective: A purposive study aims to identify the student knowledge about tuberculosis disease